Comparative evaluation of Republic of Moldova’s competitiveness within the group of economies in transition - Percinschi, Natalia; Ceban, Alina (ОАО «Трансфер», 2017)
Among European countries which have completed the transition from planned to market economy, Moldova has enjoyed less success. Although it is working to support the creation and strengthening economic transition, the expected results are achieved slowly. Republic of Moldova has signed in June 2014 the Association Agreement with the European Union, in order to complete the transition period, to increase business competitiveness and populations’ quality of life and therefore to reduce development disparities compared to other countries in the region. The article below treats the main pillars of economic competitiveness of the country in comparison with other economies in transition, on the base of Global Competitiveness Report methodology.

Среди европейских стран, которые завершили переход от плановой экономики к рыночной, Молдова пользуется меньшим успехом. Несмотря на то, что она работает, чтобы поддержать создание и укрепление экономического перехода, ожидаемые результаты достигаются медленно. Республика Молдова подписала в июне 2014 г. Соглашение об ассоциации с Европейским союзом, для того чтобы завершить транзитный период, а также для повышения конкурентоспособности бизнеса и качества жизни и, таким образом, уменьшить неравенства в области развития по сравнению с другими странами региона. В данной статье рассматриваются основные составляющие экономической конкурентоспособности страны по сравнению с другими странами с переходной экономикой на основе методологии Глобального отчета о конкурентоспособности.
Абстракт на англ., рус. яз. Библиогр.: с. 81 (10 наз.).
Keywords: конкурентоспособность; экономика переходного периода; Республика Молдова; бизнесс; инвестиции; competitiveness; transition economy; Republic of Moldova; business; investment